2020
DOI: 10.3390/rel11070348
|View full text |Cite
|
Sign up to set email alerts
|

Equal Opportunity Beliefs beyond Black and White American Christianity

Abstract: Scholars in critical race and the sociology of religion have independently drawn attention to the ways in which cultural ideologies drive beliefs about inequalities between groups. Critical race work on “abstract liberalism” highlights non-racially inflected language that tacitly reinforces White socioeconomic outcomes resulting from an allegedly fair social system. Sociologists of religion have noted that White Evangelical Christian theology promotes an individualist mindset that places blame for raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Studies show that Black Christians are more likely than White Christians to recognize structural and racial inequality (Emerson and Smith 2000; Hinojosa and Park 2004; Perry and Whitehead 2019), that White evangelicals appear distinctive in their individualistic perspectives (Cobb 2013; Tranby and Hartmann 2008), and that religious orthodoxy interacts with structural position in shaping different understandings of racial inequality (Frost and Edgell 2017). In addition, Park and colleagues (2020) find that White Christians are the least supportive of equal opportunity and that second‐generation Latino and Asian American evangelicals are similar to White people in their perspectives. They suggest that cultural assimilation among second‐generation Latinos and Asian Americans may move them more toward the color‐blindness of White people rather than the racial perspectives of Black people (Park, Chang, and Davidson 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies show that Black Christians are more likely than White Christians to recognize structural and racial inequality (Emerson and Smith 2000; Hinojosa and Park 2004; Perry and Whitehead 2019), that White evangelicals appear distinctive in their individualistic perspectives (Cobb 2013; Tranby and Hartmann 2008), and that religious orthodoxy interacts with structural position in shaping different understandings of racial inequality (Frost and Edgell 2017). In addition, Park and colleagues (2020) find that White Christians are the least supportive of equal opportunity and that second‐generation Latino and Asian American evangelicals are similar to White people in their perspectives. They suggest that cultural assimilation among second‐generation Latinos and Asian Americans may move them more toward the color‐blindness of White people rather than the racial perspectives of Black people (Park, Chang, and Davidson 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Park and colleagues (2020) find that White Christians are the least supportive of equal opportunity and that second‐generation Latino and Asian American evangelicals are similar to White people in their perspectives. They suggest that cultural assimilation among second‐generation Latinos and Asian Americans may move them more toward the color‐blindness of White people rather than the racial perspectives of Black people (Park, Chang, and Davidson 2020). Furthermore, Edwards and Oyakawa (2022) found that Black religious leaders in predominantly White denominations are more similar to White evangelicals in drawing on individualistic understandings of inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…By interrogating the assumptions of White Christian norms, new scholarship could examine the intersection of race and religion by focusing on racial/ethnic groups that share a religious affiliation. Few studies have explored this intersection (Padela and Curlin 2013;Park et al 2020;Yukich and Edgell 2020). Examining the racial inequities highlighted by this pandemic offers an opportunity to increase understanding of religion and health among members of predominately Black and other minority-dominant faith communities as a pathway to explore health disparities overall.…”
Section: Intersecting Race and Religionmentioning
confidence: 99%